The Role of Omega-3 Polyunsaturated Fatty Acids in Stroke. (28th June 2016) - Bu, Jiyuan; Dou, Yang; Tian, Xiaodi; Wang, Zhong; Chen, Gang
Abstract : Stroke is the third commonest cause of death following cardiovascular diseases and cancer. In particular, in recent years, the morbidity and mortality of stroke keep remarkable growing. However, stroke still captures people attention far less than cardiovascular diseases and cancer. Past studies have shown that oxidative stress and inflammation play crucial roles in the progress of cerebral injury induced by stroke. Evidence is accumulating that the dietary supplementation of fish oil exhibits beneficial effects on several diseases, such as cardiovascular diseases, metabolic diseases, and cancer. Omega-3 polyunsaturated fatty acids (n-3 PUFAs), the major component of fish oil, have been found against oxidative stress and inflammation in cardiovascular diseases. And the potential of n-3 PUFAs in stroke treatment is attracting more and more attention. In this review, we will review the effects of n-3 PUFAs on stroke and mainly focus on the antioxidant and anti-inflammatory effects of n-3 PUFAs.